Peranan Guru Pamong Membimbing Mahasiswa Sosiologi STKIP PGRI Sumatera Barat (Studi Tentang Kesiapan Guru Pamong Membimbing Mahasiswa PPL Untuk Praktek Mengajar) Di SMA N Se-Kabupaten Dharmasraya - Yani, Nadia Fitri; Adiyalmon, Adiyalmon; Marleni, Marleni (Pendidikan Sosiologi, 2013)
Education is a factor that has never out of human life in order to improve quality of education teacher is essential that has big responsibility to make up quality of education it self. So, LPTK Teacher Practice Program (PPL) to apply their knowledge since school in university. There are some problems in PPL such as less ready of teacher advisors to guide the students make lesson plan, less ready of teacher advisors to guide the students so that comprehend the material, the students often teach alone without teacher advisors, and less ready of teacher advisor to guide the student control the class the purpose of the research is the description about how the function of the teacher advisor to guide Sociology students in preparation to Theacher Practice Program (PPL), Teacher advisors strategy guide the student in control the class in preparation to tell Teacher Practice Program in all SMA N Dharmasraya.This research use qualitatife research in form of descpritife, location of this research are all SMA N in Dharmasraya. They are SMA N 1 Koto Baru, SMA N 2 Koto Baru, and SMA N 1 Koto Salak. informer this research where headmaster, teacher advisor and students teacher. Practice technique of data collection where used observation, interview and documentation of study.Result of this research show that there is a ready of teacher advisor before tell his job that appropriate guide the Sosiology students in PPL. As conclusion, some of school still there is teacher advisor that had not full function in advice or guide Sosiologyâs students in Teacher Practice Program (PPL)